FULFILLMENT OF CONSTITUIONAL RIGHTS OF BELIEFS PARAMASAN UPPER PRIMARY SCHOOL STUDENTS - Siti Aminah, Siti Aminah; Sarbaini, Sarbaini; Subiyakto, Bambang (JURNAL SOCIUS, 2024)
One of the most urgent social skills for students in the world of education is the ability to communicate effectively. Good communication skills enable students to convey ideas, opinions and feelings clearly and precisely to others. This is important in the learning process, collaboration in groups, and daily social interactions. Social skills are an important aspect of individual development, especially during adolescence. Classroom learning that promotes student engagement and collaboration can make a significant contribution to improving social skills. This research aims to investigate improving students' social skills in class VII of SMP Muhammadiyah 2 Banjarmasin through a collaborative learning approach. The research method used is a qualitative study with a phenomenological approach. Data was collected through classroom observations, interviews with teachers and students, and document analysis. The research results show that collaborative learning is effective in improving students' social skills in class VII of SMP Muhammadiyah 2 Banjarmasin.